Incremental relaying cooperative networks with dual transmit diversity. (January 2018) - Khodeir, Mahmoud; Hayajneh, Ali; Pourvali, Mahsa; Ghani, Nasir
Abstract: This paper studies the performance of cooperative wireless networks using incremental-relaying and dual transmit diversity with the simple orthogonal space time block coding (OSTBC) scheme. The proposed model is studied by utilizing different relaying schemes including decode and forward (DF), amplify and forward (AF), and adaptive incremental-relaying (i.e., best relay selection) with DF relaying. In particular, upper-bounded expressions are derived for the average bit error rate (BER), signal to noise ratio (SNR) outage probability, average achievable rate, and normalized throughput. Detailed results show that the dual transmit diversity approach outperforms the regular incremental relaying cooperative diversity scheme in terms of transmission power and channel efficiency for the same transmit power. Moreover, best relay selection with multiple relaying nodes outperforms fixed incremental DF relaying, especially for lower transmitted SNR values.